Kajian Sifat Fisika-Kimia Air Bahang dan Indeks Pencemaran di Perairan PLTU Sumbawa Barat - Amirul Hilmi; Andi Maria Ulfa; Muh. Iman Darmawan (Universitas Hamzanwadi, 2021)
This research examines the physical and chemical properties of the potential contamination of condenser cooling water (heat water) at the 2x7 MW West Sumbawa Steam Power Plant. The results showed that the hot water had met the predetermined quality standards, namely a pH of 8.21, a temperature of 38.50C and a content of free chlorine (Cl2) of 0.03 mg / L. There was an increase in sea water temperature in a radius of 17 meters east and west by 80C from 280C to 360C. Direct discharge of hot water has the potential to pollute the marine prawn environment around the 2x7 MW West Sumbawa PLTU. From the results of the study, it was found that the temperature of the hot water had met the specified quality standard, which was 40oC, but direct disposal caused the sea water temperature to rise, exceeding the set sea water temperature quality standard of 320C and the temperature increase should not be more than 20C from the temperature. at first.The status of sea water quality due to the entry of hot water is determined using a pollution index. From the calculation results obtained PIj of 1.125 at the sample point Outfall 2, meaning that the sea water conditions at a radius of 17 meters are lightly polluted. As a form of control and prevention of pollution due to the entry of high temperature hot water, continuous monitoring is necessary and it is necessary to create a mixing pool between sea water and hot water before the heat is discharged into the sea.